The second species of the enigmatic genus Microblattellus Ferrer, 2006 (Coleoptera, Tenebrionidae) from Cambodia: A possibility of termitophily in the genus - Maruyama, Munetoshi; Liang, Wei-Ren; Sokh, Heng; Ando, Kiyoshi (Zootaxa, 2025)
The second species of the enigmatic tenebrionid genus Microblattellus Ferrer, 2006, Microblattellus kakizoei sp. nov., is described from Cambodia. The type specimen was collected from a nest of the fungus-growing termite Macrotermes gilvus (Hagen, 1858). Although the genus is currently placed in the tribe Falsocossyphini, its assignment is highly doubtful, and its true systematic position remains uncertain.